Soroprevalência de Toxoplasma gondii em rebanhos caprinos no Estado de São Paulo - Soares Mainardi, Rodrigo; Modolo, José Rafael [UNESP]; Stachissin, Anee Valéria Mendonça; Padovani, Carlos Roberto; Langoni, Hélio [UNESP] (My University, 2003)
Four hundred forty-two serum samples were collected from dairy goats in seven regions of São Paulo State. These were tested for Toxoplasma gondii antibodies using the indirect immunofluorescent antibody test. Sixty-four (14,5%) serologically positive animals were found from all these goat farms studied.
Seroprevalence of Toxoplasma gondii in dairy goats in the São Paulo State, Brazil
Keywords: Caprine; Indirect immunofluorescent antibody test; Prevalence; Toxoplasma gondii; Toxoplasmosis; Brazil; goat; immunoassay; immunofluorescence test; nonhuman; prevalence; serology; seroprevalence; toxoplasmosis; Animals; Antibodies, Protozoan; Fluorescent Antibody Technique, Indirect; Goat Diseases; Goats; Seroepidemiologic Studies; Toxoplasma; Toxoplasmosis, Animal; Animalia; Capra; Capra hircus